Software process dynamics - Madachy, Raymond J (Wiley, 2008)
Madachy's book is a comprehensive compilation of the wisdom and knowledge gathered over more than twenty years of research in the field, and contains a wealth of material covering all important aspects of software project dynamics. Because many of the concepts are accompanied by example models, Madachy has provided the practitioner with the building blocks and the tools to move ahead. This book is a gift to software project managers everywhere